Child Abuse: Study and Management at the National Institute of Pediatrics, Mexico (2016)
Topic: violence against children and adolescents, and specifically child abuse (Ch.A), it is a growing global reality. Description: given the implications on health and the family of the victim, as well as the legal handling required, Ch.A should be considered and understood as a legal-social-medical emergency. Focus: For proper recording of each case of child abuse, the International Classification of Diseases (icd-10) was used for Ch.A with its four basic types (physical abuse, sexual abuse, psychological abuse and neglect). The diagnosis of this pathology requires interdisciplinary management (doctors, social workers, mental health professionals, lawyers). Likewise, for the comprehensive care of each case, interagency intervention is required (hospital institution, legal unit (Public Ministry Agency) or a civil organization (ngo mainly). Conclusions: All professionals who work or interact with girls, children and adolescents, and who suspect the possibility of some form of Ch.A, or who have confirmed the diagnosis, are required to make a complaint or medical-legal notice directly or anonymously, to the appropriate authority to comply with the Mexican Official Standard on Family, Sexual Violence Against Women (nom-046-ssa2-2005). Therefore, the legal status of the victim, the perpetrator and its family is required. Improper handling in the actions of the professionals involved, which may give rise to a legal problem.